2023
DOI: 10.1109/lwc.2022.3220158
|View full text |Cite
|
Sign up to set email alerts
|

RIS-Empowered Ambient Backscatter Communication Systems

Abstract: This study introduces and investigates the integration of a cell-free architecture with bistatic backscatter communication (BiBC), referred to as cell-free BiBC or distributed access point (AP)-assisted BiBC, which can enable potential applications in future (EH)-based Internet-of-Things (IoT) networks. To that purpose, we first present a pilot-based channel estimation scheme for estimating the direct, cascaded, forward channels of the proposed system setup. We next utilize the channel estimates for designing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…The authors of [16] combine the advantages of RIS and AmBC transmission, where the D2D terminals are able to flexibly select the operating mode to construct better channel conditions. The authors of [17] demonstrated that deploying RISs between the tag and the reader provides significant performance gains in a RIS-empowered AmBC system.…”
Section: A Prior Work 1) Studies On Backcom Systemsmentioning
confidence: 99%
“…The authors of [16] combine the advantages of RIS and AmBC transmission, where the D2D terminals are able to flexibly select the operating mode to construct better channel conditions. The authors of [17] demonstrated that deploying RISs between the tag and the reader provides significant performance gains in a RIS-empowered AmBC system.…”
Section: A Prior Work 1) Studies On Backcom Systemsmentioning
confidence: 99%
“…The collaborative design of RIS phase shifts enables constructive or destructive reception of reflected signals, which improves the received signal energy and SNR. Consequently, RISs will extend the tag communication range [128]- [133]. Fig.…”
Section: ) Ris-assisted Communicationmentioning
confidence: 99%
“…They can also reduce the backscatter data collection overhead [275], [276]. The adaptation of RIS in the forward link can amplify the emitter signal that reaches the tag and increases the communication range [133], [277], [278]. Therefore, we…”
Section: ) Uav/ris/relay-assisted Backcommentioning
confidence: 99%
“…Passive IoT refers to a new paradigm that focuses on IoT deployments with battery-free devices, and the race toward the definition and standardization of passive IoT has already been initiated; for instance, the third-generation partnership project (3GPP) has run initial studies of use cases and requirements in Release 18 [2,3]. For their operation, passive IoT should rely on the evolution of critical technologies, namely environment energy harvesting, low-power computing and backscatter communication (BC).…”
Section: Introductionmentioning
confidence: 99%